Internationalization in Higher Education: Equity, Affordability, Epistemic Democracy? or Social Reproduction and World-Systems Stratification - Castaneda, Maribel (Journal of International Students, 2022)
This autoethnographic paper exposes the multiple barriers encountered by an international doctoral female student in the United States: health issues especially Covid-19, institutional, political, geopolitical, knowledge production and economic factors. Reproduction theory, the world-system analysis and intellectual imperialism are used to examine these factors exposing the illusion of equity in international higher education and its role in perpetuating the imbalances and exclusion of large groups of people and entire countries. Contrary to the narrative, international students are often part of these large excluded groups of people but are not regularly included in the discussion.